THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH IN HIGHER MILITARY EDUCATION - Temirov Sirojiddin Shoymardon O‘G‘Li, (Ustozlar uchun, 2025)
This article explores the significant role of Artificial Intelligence (AI) in enhancing the teaching of English in higher military education. It highlights various AI-driven methods and tools that can be utilized to personalize learning, improve listening and pronunciation, assist in translation, and provide support to instructors. The paper emphasizes how AI can optimize the learning process, making it more efficient and tailored to individual needs while preparing military personnel for international communication and collaboration. Ultimately, the integration of AI in English education within military institutions is seen as a critical step toward improving both language proficiency and the global integration of military forces.